A standard study of the relationship between insurance and economic growth in Syria using ARDL model during the period 1991-2019 (Journal of Hama University, 2024)
The aim of this research is to test the impact of the insurance sector on economic growth in Syria during the period from 1991 to 2019, based on annual data obtained from the United Nations, the Insurance Supervisory Authority and Syrian Central Statistical Office. The dependent variable economic growth was measured in natural logarithms of real GDP at constant prices; While the insurance sector was expressed as an independent variable in the natural logarithm of the total insurance premiums; Gross investment and gross private consumption expenditure were included as control variables. In order to achieve the aim of the research, ARDL (Autoregressive Distrusted Lag Model) was applied after ensuring the stability of the variables in the first difference. Where the impact was tested on both the long and short term.The results showed that the insurance sector affects negatively and significantly the economic growth in Syria in both the long and short terms.
Keywords: insurance, economic growth , ARDL-ECM